A Challenging Case of Ureteroiliac Artery Fistula Managed With an Endovascular Approach. (October 2022) - Abou Chakra, Mohamad; Azoulai, David; Peyromaure, Michael; Barry Delongchamps, Nicolas; Bailly, Hugo; Lucas, Alexandre; Dautry, Raphaël; Duquesne, Igor
Ureteroarterial fistula (UAF) is a rare but life-threatening condition because of massive hemorrhage. Risk factors include degenerative vascular diseases, previous vascular surgery, pelvic radiation, chemotherapy, pelvic surgery, and prolonged ureteral stenting. The most common presentation of UAF is massive hematuria with hemorrhagic shock. The diagnosis is always difficult even with angiography. Endovascular repair with stenting and/or coiling is effective and safe. The surgical treatment should be used in recurrent UAF cases. We reported a rare case describing rapid management of a UAF in a patient who presented with hematuria even when we had no diagnosis on the initial CT scan. The patient was in shock. Deployment of a stent graft within the common iliac artery bypassing the UAF was performed. The patient improved rapidly.